Advancements in Sign Language Interpretation Using Glove Technology - Idrees, Ahmed Anees; Hani, Zainab Saad; Fayyad, Namir Ali Hussein; Kadhim, Hussein Haitham; Hameed, Saad Najeh (American Journal of Botany and Bioengineering, 2025)
Every human deserves a way to communicate with and express themselves to the people around them. A person can express their feelings with speaking or writing, but in the case of deaf and mute people, expressing themselves is very complex. Sign languages are the primary modes of communication among deaf and mute people. Sign languages are visual languages that use signs made by moving the hands, arms, body, and facial expressions. Sign languages are genuine languages, independent of the spoken languages, and form the basis of language development in a sign language child . The knowledge of sign language is very inadequate among the speaking and hearing people. This creates a communication gap between the two groups. This communication gap leads to the extremities of psychological and societal impacts on the deaf and mute communities. This demonstrates a definite need for a method to bridge the communication gap. Finger Glove is developed to facilitate the communication between speaking and hearing people with deaf and mute people using a pair of gloves. A glove for the deaf and mute person with sensors such as flex, accelerometer, and gyroscope is designed to detect sign language gestures and translate them into textual format. An Android application for the speaking and hearing person is developed which takes a string input of text and converts it into speech text output [1]. The complete system is tested and results are recorded and presented. The knowledge of sign language is scarce among the speaking and hearing people. The gap of knowledge of sign language creates faulty assumptions regarding the deaf and mute community, which in turn leads to bullying. This disadvantage creates a definite need for a device to translate sign languages to speech. The proposed device creates a pair of gloves, where the user wears one glove and makes sign language gestures. The glove translates the sign language gestures into speech. The glove consists of different sensors (flex, accelerometer, and gyroscope) for detecting gestures and translating them to speech format. The main aim of this research is to develop a cost-efficient, portable glove that aims to translate sign language to speech.